The Use of Prohibited Substances by Athlete are Covered in Doping Offenses - Gunawan, Candra; Muchtar, Andhyka; Nasir, Muh. (PT FORMOSA CENDEKIA GLOBAL, 2023)
Doping is the administration of oral or paralytic drugs or concoctions to an athlete with the aim of increasing unnatural accuracy. In Indonesia, the prohibition on the use of doping consisting of prohibited substances and/or methods is regulated in Law Number 11 of 2022 concerning Sports. The use of doping is contrary to the principle of